Effect of temperature and SiO2 nanoparticle size on wettability alteration of oil-wet calcite. (15th October 2017) - Al-Anssari, Sarmad; Wang, Shaobin; Barifcani, Ahmed; Lebedev, Maxim; Iglauer, Stefan
Graphical abstract: Maximum resolution zoom-into the irreversibly adsorbed silica agglomerates at 50 °C. Abstract: Nanofluid treatment of oil reservoirs is being developed to enhance oil recovery and increase residual trapping capacities of CO2 at the reservoir scale. Recent studies have demonstrated good potential for silica nanoparticles for enhanced oil recovery (EOR) at ambient conditions. Nanofluid composition and exposure time have shown significant effects on the efficiency of EOR. However, there is a serious lack of information regarding the influence of temperature on nanofluid performance; thus the effects of temperature, exposure time and particle size on wettability alteration of oil-wet calcite surface were comprehensively investigated; moreover, the stability of the nanofluids was examined. We found that nanofluid treatment is more efficient at elevated temperatures, while nanoparticle size had no influence. Mechanistically most nanoparticles were irreversibly adsorbed by the calcite surface. We conclude that such nano-formulations are potentially useful EOR agents and may improve the efficiency of CO2 -storage even at higher reservoir temperatures.